Educating the existential view to nurses in cancer care: A review - Negin Masoudi Alavi; Fatemeh Hosseini (Iranian Journal of Nursing and Midwifery Research, 2019)
Background: The aim of this study was to review the interventional studies about educating existential concepts to the nurses working in cancer care. Materials and Methods: In this systematic narrative review, the papers published in English and Farsi databases of PubMed, Elsevier, web of since, Scopus, ProQuest, ERIC, Google Scholar and Ovid, MagIran and SID, from 1990 to 2018 were reviewed. Methodological quality of the studies was independently assessed by, using checklists developed by Greenhalgh, and Cochrane Center. No statistical pooling of the outcomes was performed, due to heterogeneity of the outcomes. Results: After wide search, the 17 studies entered to this narrative study. The results showed that educating the existential concept to the nurses dealing with cancer patients can improve their self-competency in providing efficient care to these patients and their ability in decision making. It also enhances their quality of life and decreases the death anxiety and emotional exhaustion. Conclusions: There were limited and low quality interventional studies about the effects of educating existential concepts to the nurses dealing with cancer patients. These studies showed that knowing this philosophy can help nurses to address caring needs of cancer patients more efficiently. The specific method or content of education cannot be recommended because of the large differences in the methodologies between the studies.